2018
DOI: 10.1111/ecc.12953
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of healthcare professionals on patient Internet use during the cancer experience

Abstract: In this study, we document cancer healthcare professionals’ views of patients’ use of cancer‐related Internet information (CRII) and their views on how it informs the ways patients interact with healthcare professionals and services from the point of view of health professionals. We used an interpretive descriptive approach, conducting interviews and focus groups with oncology healthcare professionals (n = 21) at a University‐affiliated western Canadian cancer treatment centre. Data were analysed using themati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
1
Order By: Relevance
“…Similar to young people’s views,14 HCPs were generally satisfied by the factual information about cancer and treatment available online for young people who were at diagnosis or on treatment. In contrast to previous studies with adult cancer patients that indicated a reluctance to recommend online information,15,20,23,24 we found HCPs directed young people to websites from the point of diagnosis, especially those with a reported reputation for being accurate, such as Macmillan Cancer Support, Cancer Research UK, and NHS Choices. Professionals described variation in online use throughout the cancer timeline similar to previous reported young people’s views,14 and felt existing online information and resources for young people beyond treatment, who were relapsed, in long-term follow-up and receiving palliative care were lacking.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar to young people’s views,14 HCPs were generally satisfied by the factual information about cancer and treatment available online for young people who were at diagnosis or on treatment. In contrast to previous studies with adult cancer patients that indicated a reluctance to recommend online information,15,20,23,24 we found HCPs directed young people to websites from the point of diagnosis, especially those with a reported reputation for being accurate, such as Macmillan Cancer Support, Cancer Research UK, and NHS Choices. Professionals described variation in online use throughout the cancer timeline similar to previous reported young people’s views,14 and felt existing online information and resources for young people beyond treatment, who were relapsed, in long-term follow-up and receiving palliative care were lacking.…”
Section: Discussioncontrasting
confidence: 99%
“…Keeping young people safe online was a big concern for HCPs, and there was anxiety over their inability to control what young people looked at online, or who they may interact with. This has been reported previously,24 especially concern over the availability of videos online and the impact it could have on patients viewing procedures they were scheduled to have. Other concerns professionals have previously reported was difficulty patients could have in understanding online information, information giving young people unrealistic expectations about treatment or request treatment that was not suitable 17,24.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Increasingly, patients turn to the Internet for health information, and women use the Internet as a source of health information more than men [27]. Sharing of Internet-acquired information by patients during appointments can foster communication and improve the patient–clinician relationship [28], and supplement information provided by clinicians [29]. However, clinicians have raised concerns about the accuracy of online health information [30].…”
Section: Introductionmentioning
confidence: 99%